Safety and Immunogenicity of Pneumococcal Conjugate Vaccines in a High-risk Population: A Randomized Controlled Trial of 10-Valent and 13-Valent Pneumococcal Conjugate Vaccine in Papua New Guinean Infants. (3rd September 2018) - Pomat, William S; van den Biggelaar, Anita H J; Wana, Sandra; Francis, Jacinta P; Solomon, Vela; Greenhill, Andrew R; Ford, Rebecca; Orami, Tilda; Passey, Megan; Jacoby, Peter; Kirkham, Lea-Ann; Lehmann, Deborah; et al.
Abstract: Background: There are little data on the immunogenicity of PCV10 and PCV13 in the same high-risk population. Methods: PCV10 and PCV13 were studied head-to-head in a randomized controlled trial in Papua New Guinea in which 262 infants received 3 doses of PCV10 or PCV13 at 1, 2, and 3 months of age. Serotype-specific immunoglobulin G (IgG) concentrations, and pneumococcal and nontypeable Haemophilus influenzae (NTHi) carriage were assessed prevaccination and at 4 and 9 months of age. Infants were followed up for safety until 9 months of age. Results: One month after the third dose of PCV10 or PCV13, ˃80% of infants had IgG concentrations ≥0.35µg/mL for vaccine serotypes, and 6 months postvaccination IgG concentrations ≥0.35 µg/mL were maintained for 8/10 shared PCV serotypes in > 75% of children vaccinated with either PCV10 or PCV13. Children carried a total of 65 different pneumococcal serotypes (plus nonserotypeable). At 4 months of age, 92% (95% confidence interval [CI] 85–96) of children vaccinated with PCV10 and 81% (95% CI 72–88) vaccinated with PCV13 were pneumococcal carriers ( P = .023), whereas no differences were seen at 9 months of age, or for NTHi carriage. Both vaccines were well tolerated and not associated with serious adverse events. Conclusions: Infant vaccination with 3 doses of PCV10 or PCV13 is safe and immunogenic in a highly endemic setting; however, to significantly reduce pneumococcal disease in these settings, PCVs with broader serotype coverage and potency to reduce pneumococcal carriage are needed. Clinical Trials Registration: NCT01619462. Abstract : This head-to-head study shows that PCV10 and PCV13 are safe, immunogenic, and suitable for immunising infants in a high-risk setting.